Implementation of Picture Series to Improve Speaking Skills - Maria Osmunda Eawea Monny; Anak Agung Gde Raka Wahyu Brahma (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2025)
The research aims to examine the effectiveness of the implementation of the picture series to improve the speaking skills of the students in INSTIKI. The participants of this research are 22 students of Bahasa Inggris I Class B. This is mixed research that measured quantitatively and qualitatively. The method used was Class Action research (CAR) which was implemented in 3 cycles, which are pre-cycle (observation), cycle I, and cycle II. The results of the research showed that in cycle 1 The data showed that in cycle I, without a picture series, the students made 3 kinds of errors, those are: 1) agreement of subject and verb (20 errors); 2) connectors (15 errors); and 3) time expressions (9 errors). While in cycle II with the group division, the errors made were lessened compared to the second group (with picture series), those are: 1) agreement of subject and verb (8 errors); 2) connectors (5 errors); and 3) time expressions (2 errors). On the other hand, the first group (without picture series) did not have much improvement. The first group made errors as follows: 1) agreement of subject and verb (17 errors); 2) connectors (12 errors); and 3) time expressions (7 errors). The implementation of two two-sample tests (two-group division) has shown the differences between them. It can be concluded that the implementation of picture series can improve students’ speaking skills.